From Admissions to Graduation: An Analysis of a Social Justice Infused Masters-Level Counseling Program - Paone, Tina; Pulliam, Nicole; Smith, Vernon; Homer, Kyle; Zambak, Vechihi (ILIN Education Indonesia, 2024)
Researchers assessed the impacts of a social justice-infused masters-level counseling program (N = 210) over a five-year period. A social justice-infused masters-level counseling program is defined as a program that teaches social justice concepts as the focal point of each class, with the counseling content being gleaned through that lens. Social justice is not an afterthought in coursework but rather the primary focus. Impacts were assessed using the Intercultural Development Inventory (IDI LLC, 2020). Results offer useful data that could inform other counseling programs looking to assess students' overall intercultural, cultural, or multicultural counseling competence throughout their programs.